Śrīvijaya Kavirājamārgaṃ : The Way of the King of Poets - Patel, Deven M.,; Sundaram, R.V.S., (Brill | Manohar Publishers & Distributors, 2017)
The Kavirājamārgaṃ (The Way of the King of Poets), the first extant work of early Kannada, was composed in the ninth century by poet-scholar Śrīvijaya in the court of King Nrpatunga of Mānyakhēta. The Kavirājamārgaṃ magnificently defines and illustrates poetic ornaments of sound and sense (alank \ āras), elucidates important features of early Kannada grammar and prosody, and offers us a glimpse into the early history, geography, and aesthetic tastes of the Kannada region and its people. It is therefore, a work of monumental importance for understanding the development of a regional poetic consciousness within the contexts of classical cosmopolitan structures of thought and aesthetic taste.